Social dentistry in the context of Health Promotion - doi:10.5020/18061230.2008.p75 - Edjane Tenório de Oliveira; José Ferreira Lima Júnior; Francisca Neta Cruz Sampaio Soares; Evanira Rodrigues Maia (Universidade de Fortaleza, 2012)
Objective: To argue upon the social hole of Dentistry in health promotion. Data Synthesis: It is necessary to understand health promotion as a process by which people and communities are enabled to analyze and to reflect over their real problems for, only then, think strategies for overcoming such difficulties. As oral diseases are direct products of the social insertion of affected people/communities, the dentist can greatly contribute to the increase in the quality of life of these groups. What is observed in the dentist professional acting is the unfamiliarity on how to make health strictu sensu. Therein, academic changes in graduation courses are proposed, in which subjects directed to the social aspects of the profession may be adequately explored. It is understood that such alterations may be reflected in health services practice, contributing for the conceptual change of hegemonic attention model. Final considerations: Dentistry has a relevant social role, as it can contribute, beyond clinical procedures in the oral cavity, for the real increment of people/communities quality of life.